2012
DOI: 10.1364/josab.29.000305
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the transparency in the visible range of x-ray absorbing nanocomposites built upon the assembly of LaF_3 or LaPO_4 nanoparticles with poly(methyl methacrylate)

Abstract: A theoretical multiscale approach combining density functional theory and four-flux calculations based on the radiative transfer theory is used to prospect the optical properties of nanocomposite materials composed of inorganic nanoparticles of lanthanum-containing compounds (LaF 3 or LaPO 4 ) embedded in Poly(methyl methacrylate) (PMMA). This theoretical investigation shows that a potential route to produce lead-free x-ray shielding screens with high transparency in the visible range (>70% of incident light) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…For example, a recent theoretical investigation has shown that it is necessary to add an on-site Hubbard correction (U eff = 10.3 eV) on the 4f(La) orbitals to properly describe their localizations and then their energy positions, allowing the XPS/BIS and reflectance experimental spectra of LaF 3 to be properly simulated. 118 In our case, the very large deviation observed for LaF 3 (Fig. 3(a)) shows that the La 3+ ion (4f 0 ) has a similar symptomatic behaviour as Ca 2+ and Sc 3+ ions.…”
Section: Nmr Shielding Calculations On Crystalline Systemssupporting
confidence: 53%
See 1 more Smart Citation
“…For example, a recent theoretical investigation has shown that it is necessary to add an on-site Hubbard correction (U eff = 10.3 eV) on the 4f(La) orbitals to properly describe their localizations and then their energy positions, allowing the XPS/BIS and reflectance experimental spectra of LaF 3 to be properly simulated. 118 In our case, the very large deviation observed for LaF 3 (Fig. 3(a)) shows that the La 3+ ion (4f 0 ) has a similar symptomatic behaviour as Ca 2+ and Sc 3+ ions.…”
Section: Nmr Shielding Calculations On Crystalline Systemssupporting
confidence: 53%
“…Another striking point is that the slope obtained here, which is relatively close to that obtained by Griffin et al, 26 differs significantly from the slope reported by Zheng et al 56 This difference arises mainly from the consideration of the calculated s iso values for LaF 3 , ScF 3 and CaF 2 , two of these compounds containing cations (Ca 2+ and La 3+ ) already known to be inaccurately described with PBE-DFT. 60,118 In the work of Griffin et al, two of these three compounds (CaF 2 and LaF 3 ) were considered while only CaF 2 was studied by Zheng et al leading to a larger absolute slope.…”
Section: Nmr Shielding Calculations On Crystalline Systemsmentioning
confidence: 99%
“…This article is protected by copyright. All rights reserved Mass density ρ (gm cm -3 ) 4.93 [14] Absorption coefficient α (cm -1 ) at 532nm 2.362X10 3 [24] Reflectivity used in model R 0.9 [25] Melting point T m (K) 1853 [1] Boiling point T b (K) 2500 [26] Heat of phase transition ΔH lv (J gm -1 ) 5.89 X 10 4 [27] Laser attenuation parameters in ablation plume, (i) a (cm -1 ) and (ii) b (cm 2 /J) (i) a=3000…”
Section: Accepted Articlementioning
confidence: 99%
“…In principle, four-flux models are more accurate for thin films in which there is a substantial unscattered component. Four-flux models have been applied recently to design thermal barrier coatings [29], x-ray shielding [30], dental composites [31], and nanotechnology for energy applications [32]. However, a major drawback of the current formalism is that it cannot be easily extended to multiple layers [33].…”
Section: Introductionmentioning
confidence: 99%